2020
DOI: 10.1186/s12957-020-01868-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival among patients with gastrointestinal stromal tumors diagnosed after another malignancy: a SEER population-based study

Abstract: Background: To explore overall survival (OS) and GISTs-specific survival (GSS) among cancer survivors developing a second primary gastrointestinal stromal tumors (GISTs). Methods: We conducted a cohort study, where patients with GISTs after another malignancy (AM-GISTs, n = 851) and those with only GISTs (GISTs-1, n = 7660) were identified from the Surveillance, Epidemiology, and End Results registries (1988-2016). Clinicopathologic characteristics and survival were compared between the two groups. Results: Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…A total of 69 articles were reviewed. Seventeen articles reported the prevalence of genitourinary cancer associated with GIST ranging 2.1-15.6% (Table 2) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . Prostatic adenocarcinoma was the most common primary genitourinary cancer (2.1-14%), followed by RCC (0.6-11.4%).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 69 articles were reviewed. Seventeen articles reported the prevalence of genitourinary cancer associated with GIST ranging 2.1-15.6% (Table 2) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . Prostatic adenocarcinoma was the most common primary genitourinary cancer (2.1-14%), followed by RCC (0.6-11.4%).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the improvement in tumor control due to the progress of targeted therapies leads to an increase in the longevity of patients who are more likely to develop a second cancer. This type of situation requiring the combination of several TKIs is likely to be encountered more frequently in the years to come [ 23 ]. The main objective will be to maintain optimal anti-tumor activity while ensuring acceptable tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…GISTs, as a low incidence gastrointestinal tumour, are gradually gaining the attention of oncologists, surgeons, and gastroenterologists. In addition to studies on the clinical characteristics and prognosis of gastrointestinal stromal tumours, such as the long-term survival of patients with gastrointestinal stromal tumours diagnosed after malignant tumours [ 45 ], the whole-process management of gastrointestinal stromal tumours is gradually enriched and improved, such as preoperative adjuvant therapy for locally advanced and recurrent/metastatic gastrointestinal stromal tumours [ 46 ]. However, in clinical diagnosis and treatment, concise and efficient prognostic evaluation criteria are still the most concerned issue for clinicians; we calculated and compared all the commonly used prognostic markers and found that the Naples score may be the most practical comprehensive evaluation system.…”
Section: Discussionmentioning
confidence: 99%